Effect of the inclusion of beet pulps of different origin on the digestibility and nutritional value of diets for fattening rabbits - Arce, O.; Alagón, G.; Ródenas, L.; Martínez-Paredes, E.; Moya, V. J.; Pascual, J. J.; Cervera, C. (Cuban Journal of Agricultural Science, 2019)
To determine the digestibility variability of beet pulps (BP) in the nutritional value of diets for fattening rabbits, the substitution of 20 % of a control feed with BP from five different origins was evaluated. Rabbits of 42 days of age and 1.49 ± 0.208 kg of weight were used, housed in individual cages and with ad libitum feeding. The digestibility of feed components was determined by the conventional in vivo method of total fecal collection. The digestibility of each of beet pulps was determined by the substitution method. There was no effect of the substitution of components of the control feed with 20 % of BP from different sources in the voluntary intake of rabbits (P> 0.05). The inclusion of BP in diets increases the digestibility of dry matter, organic matter, gross energy and all fibrous fractions, and decreases the digestibility of crude protein. However, the effect was more or less important depending on the origin of BP (P <0.05), especially on the digestibility of all fibrous fractions, being the BP collected in summer the one with the highest digestibility. The origin of the BP also affected its nutritional value, giving values of digestible energy between 11.8 and 14.5 MJ kg DM-1 and digestible protein between 3.8 and 6.6 %. Key words: digestibility, energy, beet pulp, Oryctolagus cuniculus